Mediating Effects of Customer Management on the Relationship between Employee engagement, Financial Strategic decisions, and Organizational Performance: A conceptual Analysis. - Azameti, M. S. K.; Balila, Jolly (European Journal of Applied Sciences, 2022)
This paper adopts an indepth review of literature with a Conceptual Case Anlysis study paradigm.The review of literature covers Employee Engagement, Strategic financial decision making, Customer Management and supporting theories and organizational performance.The study conceptualizes that the two dependent variables medited by customer management shown in the conceptual digram impact organizational achievement in service enterprieses including educational institutions.It emphasizes also that an organization may have all that it takes to achieve its goals which may not include only conducive organizational climate, egalitarian- leadership ,human capital maximization with streaming organizational culture ethos and structural encumbrances, but also collaborating efforts among all the sectors and mediators to achieved the desired goals.These factors provide the thrust for achieving goals in an organization. Previous studies emphasized organizational culture, structure and human capital performance as key levers in achieving competitive advantage, side- stepping collaborating between customer management,financial strategic decision making and the impact on organizational performance. Recent studies in the health sector in west African countries emphasized good administrative planning and control,rewards and compensation,business strategy and off setting environmental uncertainty.The earlier study focuses on the mediating roles of organizational capabilities and its determinants.However,the This work uses a Conceptual Case Analysis study methodology to conduct an in-depth analysis of the literature. Employee engagement, strategic financial decision making, customer management, and supporting theories, as well as organizational performance, are all covered in the literature review. The study hypothesizes that the two dependent variables mediated by customer management, as depicted in the conceptual diagram, have an impact on organizational success in service businesses, including educational institutions. It also emphasizes that an organization may have everything it takes to achieve its objectives, which may include not only a favorable organizational climate, egalitarian leadership, human capital maximization with streaming organizational culture ethos, and structural encumbrances, but also collaborative efforts among all sectors and mediators to achieve the desired objectives. These variables give the impetus for an organization’s aims to be met. Previous research has focused on organizational culture, structure, and human capital performance as essential levers for creating competitive advantage, ignoring collaboration between customer management, financial strategic decision-making, and the influence on organizational performance. knowledge gap left which is filled by this current study are the conceptualization of customer management as an intervening variable together with employee engagement and strategic decision manking as dependent variables. In order to establish the relationship between dependent and the independent variables, this study recommends further research work to analyze an empirical data on employee engagement,strategic decision making and customer management and its resultant effects on organizational performance.